Comparative genomic analysis of clinical Pseudomonas aeruginosa isolates from Iraq: insights into genome diversity, antimicrobial resistance, and phylogenetic relatedness - Shahnaz Burhan Ali¹; Akhter Ahmed Ahmed (Molecular Biology Reports, 2026)

Bioengineered Citrus maxima mediated Silver Nanoparticles exhibit potent Antimicrobial, Anti-adipogenic and Antidiabetic effects - Shahnaz Majeed; Nurul Shahirah Binti Nazri; Ravindran Muthukumarasamy; Mohammad Danish; Sreenivas Patro Sisinthy; Abdulaziz M. Alanazi; Mohamad Nasir Bin Mohamad Ibrahim; Mohammed Tahir Ansari; Ohoud A. Jefri (Journal of Pharmaceutical Innovation, 2026)

Recent Developments on Immobilization of Heavy Metal Resistant Bacteria for Enhanced Metal Degradation - Shahnaz Bashir; Mohammad Noor Salaam Khan; Khalid Muzamil Gani (Water, Air, & Soil Pollution, 2026)

Green synthesized zinc oxide nanoparticles: antibacterial, antifungal, and antioxidant activities against multidrug-resistant pathogens - Shahnaz Majeed; Bashir Ahmad Bin Rozali; Ravindran Muthukumarasamy; Norul Aini Zakariya (Next Research, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Eco-friendly biosynthesis of gold nanoparticles using flower extract of Ixora coccinea for environmental remediation: methylene blue dye degradation and antimicrobial applications - Nur Aina Madihah Rosihan Anwar; Shahnaz Majeed; Mohammed Danish; Mohamad Shazeli Che Zain; Mohd Gulfam Alam; Ravindran Muthukumarsamy; Sreenivas Patro Sisinthy; Mohammed Tahir Ansari (Nanotechnology for Environmental Engineering, 2026)

Mind the Gap: Human and AI Uncertainties in Cardiac MRI Segmentation - Qiao Lin; Xin Chen; Chao Chen; Nikesh Jathanna; Peter P. Swoboda; Shahnaz Jamil-Copley; Jonathan M. Garibaldi (Cardiovascular Engineering and Technology, 2026)

Synergistic effect of gamma irradiation and sodium alginate coating on postharvest quality and shelf-life extension of plum fruit (cv. Santa Rosa) - Iflah Jan; Shahnaz Parveen; Peerzada Rashid Hussain; Abdul Rouf; Nageena Nazir; Mushtaq Ah. Bhat; Mehvish Mushtaq Banday; Qurazah Akeemu Amin; Tashooq Ahmad Bhat (Food Chemistry, 2026)

Glutathione at the Crossroads of Redox Homeostasis and Glucose Metabolism in Diabetes Mellitus - Shahnaz Alom; Farak Ali; Freddy Teilang Nongkhlaw; Yangchen Doma Bhutia; Bibhuti Bhusan Kakoti (Indian Journal of Clinical Biochemistry, 2026)

Retraction notice to “Incorporation of UiO-66-NH2 MOF into the PAN/chitosan nanofibers for adsorption and membrane filtration of Pb(II), Cd(II) and Cr(VI) ions from aqueous solutions” [J Hazard Mater 368 (2019) 10–20] - Sana Jamshidifard; Shahnaz Koushkbaghi; Seyedehgolshan Hosseini; Sina Rezaei; Alireza Karamipour; Azadeh Jafari rad; Mohammad Irani (Journal of Hazardous Materials, 2026)

The Prothrombotic Phenotype of Thirdhand Electronic Cigarette Exposure is Sex Independent and Involves Systemic Mediated Effects on Platelet Function: Evidence from a Mouse Model - Shelby S. Umphres; Ahmed B. Alarabi; Hamdy E. A. Ali; Shahnaz Qadri; Fadi T. Khasawneh; Fatima Z. Alshbool (Cardiovascular Toxicology, 2026)
Electronic cigarettes (e-cigs) are major contributors to inflammatory-mediated responses, which are implicated in a vast array of pathophysiological conditions, including cardiovascular disease (CVD). More recently e-cigs have been recognized as a source of thirdhand exposure (THEC); the process by which expelled toxins settle on materials (i.e., carpets, curtains, clothes etc.) and undergo chemical reactions, rendering them more harmful overtime. Herein, mice were exposed to THEC for four months, and platelet reactivity, systemic mediated effects on platelet function, and cytokine expression profiles were analyzed in both sexes. Our data revealed a hyperactive platelet phenotype as determined by shortened bleeding and occlusion times, enhanced platelet aggregation, and dense granule secretion with no significant difference between males and females. Cytokines, amongst other inflammatory molecules, are well documented mediators by which platelet function is modulated and they also enhance susceptibility to CVD. To this end, and to elucidate the mechanism by which platelet reactivity was augmented, washed platelets that were exposed only to clean air (CA) and resuspended in THEC exposed plasma, displayed significantly increased platelet aggregation, dense granule secretion, and p-selectin expression. Indeed, this data suggests that THEC exposure elicits a systemic effect, enhancing platelet response, and was further validated by a dysregulated cytokine profile using plasma, free of platelets, in a sex-dependent manner. Collectively and for the first time, we highlight that both males and females are at similar risk of THEC-mediated prothrombotic phenotype, which is underlined-at least in part- by an indirect systemic effect of exposure on platelet reactivity that involves changes in the cytokine profile. These findings underscore this form of exposure as a threat to cardiovascular health.

Sustainability and “food mileage” of ground beef packaging in the beef industry from post-harvest to retail display - Shahnaz Mukta; Katie M. Updegraff; Mark R. Early; Greg W. Curtzwiler; Keith L. Vorst (Meat Science, 2026)

Effects of selected food-compatible printing materials on product properties towards 3D binder jetting - Dang Chung Nguyen; Rico F. Tabor; Yunlong Tang; Louise Bennett; Shahnaz Mansouri (Journal of Food Engineering, 2026)

Cellulose-derivative based bigels: stability and printability assessment for extrusion-based 3D printing - Pasindu Perera; Shahnaz Mansouri; Yunlong Tang (Food Hydrocolloids, 2026)

In silico approach for a multi-epitope, multi-stage vaccine construct against human hookworm infection - Kaisar Ahmad Sheikh; Shahnaz Khanam; Nasir Salam (Next Research, 2025)

Supercritical fluid extraction and micro-encapsulation of Saussurea costus roots for next gen functional foods: antioxidant potential, surface morphology and anti-diabetic potential - Madikha Mushtaq; Quraazah Akeemu Amin; Towseef Ahmad Wani; Tashooq Ahmad Bhat; Shahnaz Parveen; Mushtaq Ahmad Beigh (Food Chemistry, 2025)

Comparative analysis of blanching methods of sweet corn kernels from Himalayan region: Impact on enzyme activity, antioxidant potential and carotenoid content - Aarizoo Mushtaq; Abida Jabeen; Mohmad Sayeed Bhat; Tawheed Amin; Aasima Rafiq; Nageena Nazir; Fouzia Shafi; Farhat Shaheen; Shahnaz Parveen (Food and Humanity, 2025)

Prevalence of carbapenemase genes in Klebsiella pneumoniae and Escherichia coli isolated from intensive care unit patients in Iran: a systematic review (2014–2025) - Shahnaz Halimi; Maryam Siroosi (Molecular Biology Reports, 2025)

Prevalence and characteristics of ST131-O16 and ST131-O25b clones among extended-spectrum β-lactamase-producing Escherichia coli isolates causing bloodstream infection in Iran - Mohammad Taha Ebrahimi; Shahnaz Halimi; Maryam Yavari-Bafghi; Reza Beigverdi; Hossein Ali Rahdar; Mohammad Emaneini; Fereshteh Jabalameli (Molecular Biology Reports, 2025)

Mesenchymal stem cells and mesenchymal stem cell-derived exosomes: attractive therapeutic approaches for female reproductive dysfunction - Sepideh Hassanpour Khodaei; Shahnaz Sabetkam; Hossein Kalarestaghi; Khadijeh Dizaji Asl; Zeinab Mazloumi; Mohammadmahdi Bahramloo; Nahid Norouzi; Elahe Naderali; Ali Rafat (Molecular Biology Reports, 2025)

SBEβCD-Enabled Resveratrol Complexes: Ternary Systems with Hydrophilic Polymers for Enhanced Stability and Antimicrobial Efficacy - Teejan Ameer Abed Alahmed; Thong Ke Xin; Liew Lai Sheong; Thevashree Rajanderan; Ahmad Salawi; Awaji Y Safhi; Osama A Madkhali; Yosif Almoshari; Mohammad Intakhab Alam; Fahad Y Sabei; Durgaramani Sivadasan; Shahnaz Majeed; et al. (Journal of Pharmaceutical Innovation, 2025)

In-vitro and in-silico analysis of phytoconstituents of Enhydra fluctuans as an antidiabetic agent - Shahnaz Alom; Farak Ali; Rajashri Bezbaruah; Bibhuti Bhusan Kakoti (Advances in Traditional Medicine, 2025)

Retraction Note: Increase of autophagy and attenuation of apoptosis by Salvigenin promote survival of SH-SY5Y cells following treatment with H2O2 - Ghazaleh Rafatian; Fariba Khodagholi; Mahdi Moridi Farimani; Shahnaz Babaei Abraki; Mossa Gardaneh (Molecular and Cellular Biochemistry, 2025)

Some aspects of the reproductive biology of a crab Leptodius exaratus (H. Milne Edwards, 1834) (family Xanthidae) from the Karachi coast, Pakistan - Javed Mustaquim; Shahnaz Rashid; Saedul Bibi; Sumaiya Adil; Shanila Khan (Invertebrate Reproduction & Development, 2025)

Exploring Bacterial Diversity in the Rhizobiome of Apple Rootstocks Through Metagenomic Amplicon-Based Sequencing - Saba Banday; Insha Tak; Sajad Un Nabi; Bilal A. Padder; Rouf A. Malik; Sajad M. Zargar; Efath Shahnaz; Fayaz A. Mohiddin; Aisha Nabi; Shugufta Parveen; Sheikh Mansoor (Applied Fruit Science, 2025)

Mycogenic Fabrication of Zinc Nanoparticles for Their Antifungal Activity Against Alternaria mali - Shahnaz Anjum; Ashish Vyas; Tariq Ahmad Sofi (Indian Journal of Microbiology, 2025)

Bacterial bioremediation strategies for heavy metal detoxification: a multidisciplinary approach - Akansha Garg; Prerna Chauhan; Charanjeet Kaur; Shahnaz Perveen; Pankaj Kumar Arora; Sanjay Kumar Garg; Vijai Pal Singh; Alok Srivastava (Environmental Sustainability, 2025)

A tetrahydropyrimidine derivative demonstrates neuroprotection against ketamine-induced schizophrenia through moderating oxidative and inflammatory markers - Tayyaba Tahir; Qurat-Ul-Ain; Ammara Saleem; Shahnaz; Muhammad Imran Khan; Kanwal Akhtar; Irfan Hamid; Rabia Iqbal; Zulcaif Ahmad; Muhammad Furqan Akhtar (Metabolic Brain Disease, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Effect of Junk Food on Hormonal and Metabolic Manifestations in Polycystic Ovarian Syndrome Phenotypes: A Case–Control Study of Kashmiri Population - Khair Ul Nisa; Najeebul Tarfeen; Shahnaz Ahmad Mir; Zulaykha Khurshid; Mir Bilal Ahmad; Saba Wani; Humaira Bhat; Bashir Ahmad Ganai (Indian Journal of Clinical Biochemistry, 2025)

Hybrid Xception-LSTM Model for Remote Sensing: Advanced Urban Heat Island and Land Use Analysis - Ashutosh Kumar Singh; Ch L. N. Deepika; K. V. Shahnaz; L. Bhagyalakshmi; K. Sharada; S. Sarupriya; Sanjay Kumar Suman (Remote Sensing in Earth Systems Sciences, 2025)

Food safety profile of university food handlers in Bangladesh: A multicenter cross-sectional study - Tahsin Ahmed Rupok; Shahnaz Parvin Sweety; Mst. Mahfuza Rahman; Most. Tasfia Rahman; Fahmida Zaman; Muhammad Radone Ahmed; Tanvirul Islam; Md. Nurnobi Islam; Md. Masud Rana; Abdur Rahman Riaz; Md. Golam Sadik (Food and Humanity, 2024)

Correction: Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Protective Effect of Berberine Nanoparticles Against Cardiotoxic Effects of Arsenic Trioxide - Seyed Hadi Hosseini; Maryam Nazarian; Shahnaz Rajabi; Amir Masoud Jafari-nozad; Behzad Mesbahzadeh; Saeed Samargahndian; Tahereh Farkhondeh (Cardiovascular Toxicology, 2024)

Influence of various soilless media and fertigation levels on growth and yield of tomato (Solanum lycopersicum L.) under polyhouse condition - Marifa Gulzar; Shahnaz Mufti; Shailendra Kumar; Latief Ahmad; Rakshanda Anayat; Nageena Nazir; Rohitashaw Kumar (Vegetos, 2024)

Potentials of orange wastes in wastewater treatment technology: A comprehensive review - Tanweer Ahmad; Mohammed Danish; Murali Dadi; Khalid Siraj; Thanigaivel Sundaram; Deena Santhana Raj; Shahnaz Majeed; Subbaiya Ramasamy (Journal of Water Process Engineering, 2024)

Association Between Dietary Magnesium Intake with Serum Brain-Derived Neurotrophic Factor (BDNF) and Adropin Levels and Metabolic Health Status in Iranian Adults - Maryam Rahimi; Shahnaz Amani Tirani; Farnaz Shahdadian; Zahra Hajhashemy; Parisa Rouhani; Sobhan Mohammadi; Elahe Mokhtari; Parvane Saneei (Biological Trace Element Research, 2024)

The potential of coated iron nanoparticles for modulating of negative effects of salinity stress in Ajowan - Roya Moloudzadeh; Shahnaz Fathi; Fataneh Yari; Sharareh Najafian; Azam Seyedi (Horticulture, Environment, and Biotechnology, 2024)

Bacterial communities of two populations of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Shahnaz Zare Banadkuki; Shima Rahmani; Ali R. Bandani (Journal of Asia-Pacific Entomology, 2024)

Bioenergy and Value-Added Chemicals Derived Through Electrocatalytic Upgradation of Biomass: a Critical Review - Mudasir Akbar Shah; Wasif Farooq; Tasrin Shahnaz; Muthumariappan Akilarasan (BioEnergy Research, 2024)

Advances in the targeted theragnostics of osteomyelitis caused by Staphylococcus aureus - Tahir Abdulrehman; Shahnaz Qadri; Yousef Haik; Ali Sultan; Sini Skariah; Shourya Kumar; Zachary Mendoza; Kamlesh K Yadav; Anoop Titus; Shameer Khader (Archives of Microbiology, 2024)

QbD Assisted Systematic Review for Optimizing the Selection of PVP as a Ternary Substance in Enhancing the Complexation Efficiency of Cyclodextrins: a Pilot Study - Glovanna Mulenga; Teejan Ameer Abed Alahmed; Farheen Sami; Shahnaz Majeed; Md Sajid Ali; Janice Lo Jia Le; Carol Lee Qhai Rhu; Rajesh Sreedharan Nair; Nadeem Hasan; Mohammed Tahir Ansari (AAPS PharmSciTech, 2024)

On the characteristics and long-term trend of total cloud cover in Iran - Shahnaz Rashedi; Armin Sorooshian; Sapna Tajbar; Osman Soufi bobakran (Acta Geophysica, 2024)

3-Acetyl coumarin alleviate neuroinflammatory responses and oxidative stress in aluminum chloride-induced Alzheimer’s disease rat model - Zakiah Zeb; Ali Sharif; Bushra Akhtar; Shahnaz (Inflammopharmacology, 2024)

Effect of arbuscular mycorrhizal colonization on tomato defense metabolites and population parameters of Tuta absoluta (Meyrick) - Fateme Shafiei; Shahnaz Shahidi-Noghabi; Guy Smagghe (Arthropod-Plant Interactions, 2024)

A review of pre- and post-surface-modified neem (Azadirachta indica) biomass adsorbent: Surface functionalization mechanism and application - Abdul Rasheed Karim; Mohammed Danish; Mohd Gulfam Alam; Shahnaz Majeed; Abdulaziz M. Alanazi (Chemosphere, 2024)

Arbuscular Mycorrhizal Fungi Inducing Tomato Plant Resistance and Its Role in Control of Bemisia tabaci Under Greenhouse Conditions - Fateme Shafiei; Shahnaz Shahidi-Noghabi; Ebrahim Sedaghati; Guy Smagghe (Neotropical Entomology, 2024)

A facile synthesis of chromeno[3,4-c]spiropyrrolidine indenoquinoxalines via 1,3-dipolar cycloadditions - Shahnaz Rahimi; Mehdi Ghandi; Maryam Fallahnezhad; Alireza Abbasi (Molecular Diversity, 2024)

Molecular Mechanisms in the Etiology of Polycystic Ovary Syndrome (PCOS): A Multifaceted Hypothesis Towards the Disease with Potential Therapeutics - Khair Ul Nisa; Najeebul Tarfeen; Shahnaz Ahmad Mir; Ajaz Ahmad Waza; Mir Bilal Ahmad; Bashir Ahmad Ganai (Indian Journal of Clinical Biochemistry, 2024)

Exploring graphene's antibacterial potential for advanced and sustainable solutions in water treatment - Tasrin Shahnaz; Gasim Hayder (Journal of Water Process Engineering, 2023)

Investigation the adsorption mechanism of a non-ionic surfactant on graphene oxide and its derivatives (kinetic, isotherm curves, thermodynamic, and effect of salts studies) - Najmeh Rezazadeh; Shahnaz Danesh; Mohammad Eftekhari (Environmental Nanotechnology, Monitoring & Management, 2023)

Genome-wide characterization and expression analysis of cyclic nucleotide-gated ion channels (CNGCs) gene family in Arabidopsis thaliana L. and Helianthus annuus L. for drought stress - Sadaf Oranab; Hafiz Muhammad Ahmad; Sajid Fiaz; Athar Hussain; Muhammad Rizwan; Shazia Arif; Saira Ishaq; Shahnaz Zakia; Asmaa M. Abushady; Itoh Kimiko; Kotb A. Attia (Brazilian Journal of Botany, 2023)

Unveiling the synergistic effect of ionic liquid and metal-organic framework on the efficiency of BiVO4: BiVO4-MIL-100(Fe) as a visible light-induced photocatalyst for Basic Red 46 degradation - Amir Hekmat; Shahnaz Ghasemi; Manouchehr Vossoughi (Journal of Environmental Chemical Engineering, 2023)

Rapid extraction of BTEX in water and milk samples based on functionalized multi-walled carbon nanotubes by dispersive homogenized-micro-solid phase extraction - Shahnaz Teimoori; Hamid Shirkhanloo; Amir Hessam Hassani; Mostafa Panahi; Nabiollah Mansouri (Food Chemistry, 2023)

Retraction Note: The Effect of Zinc Supplementation on Expressed Levels of Peroxisome Proliferator-Activated Receptor Gamma and Glucose Transporter Type 1 Genes in Newborns of Women with Gestational Diabetes Mellitus - Zahra Heidarzadeh; Mansooreh Samimi; Seyed Morteza Seifati; Mahmood Dehghani Ashkezari; Shahnaz Ahmadi; Samaneh Mahmoodi; Esmat Aghadavod; Mehri Jamilian; Zatollah Asemi (Biological Trace Element Research, 2023)

Anar Phali (Opuntia ficus) juice extract as a novel pollution-free source of natural betalain dye for wool yarn - Yousra Riaz; Samra Barkaat; Shahid Adeel; Fazal-ur-Rehman; Muhammad Ibrahim; Muhammad Zuber; Meral Ozomay; Shahnaz Parveen Khattak (Environmental Science and Pollution Research, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Molecular Characteristics of Staphylococcus aureus Strains Isolated from Nasal Cavity and Wound Infections Among Diabetic Patients - Elahe Taki; Fereshteh Jabalameli; Mohammad Reza Mohajeri Tehrani; Mohammad Mehdi Feizabadi; Shahnaz Halimi; Mahnaz Sanjari; Mohammad Reza Amini; Reza Beigverdi; Mohammad Emaneini (Current Microbiology, 2023)

Effect of temperature on predation of Chilocorus bipustulatus L. (Col.: Coccinellidae) feeding on Agonoscena pistaciae (Hem.: Psyllidae) - Haniieh Atrchian; Kamran Mahdian; Shahnaz Shahidi Noghabi (Phytoparasitica, 2023)

Intestinal colonization of vancomycin-resistant Enterococcus in children admitted to Mofid children’s hospital intensive care unit at admission and at discharge - Masoud Alebouyeh; Fariba Shirvani; Romina Hassanzadeh; Taher Azimi; Ghazale Ghandchi; Nafiseh Abdollahi; Zari Gholinejad; Azita Behzad; Zahra Sheikhi; Fatemeh Fallah; Leila Azimi; Abdollah Karimi; et al. (Molecular Biology Reports, 2023)

On the Nature of Caspian Clouds - Rashedi Shahnaz; Mohammadi Golamhasan; Jahanbakhshasl Saeed; Khorshiddoust Ali Mohammad; Sorooshian Armin; Dmitrovic Sanja; Tajbar Sapna (Journal of Meteorological Research, 2023)

An immobilization of aminopropyl trimethoxysilane-phenanthrene carbaldehyde on graphene oxide for toluene extraction and separation in water samples - Shahnaz Teimoori; Hamid Shirkhanloo; Amir Hessam Hassani; Mostafa Panahi; Nabiollah Mansouri (Chemosphere, 2023)

Molecular variability of Sphaceloma ampelinum (de Bary) causing grape anthracnose in temperate region of India - Injla Qadri; Saba Banday; Efath Shahnaz; Bilal A. Padder; Asif Shikari (Indian Phytopathology, 2023)

“Ficus johannis Boiss. leaves ethanolic extract ameliorate streptozotocin-induced diabetes in rats by upregulating the expressions of GCK, GLUT4, and IGF and downregulating G6P” - Afshan Asghar; Ali Sharif; Sana Javaid Awan; Bushra Akhtar; Muhammad Furqan Akhtar; Sajid Ali; Shahnaz (Environmental Science and Pollution Research, 2023)

Organic polymer doped graphene-based composite for the effective elimination of diclofenac: A detailed study with phytotoxic assessments - Das Bedadeep; Tasrin Shahnaz; V. Manu Sankar; Lingaraj Sahoo; Selvaraju Narayanasamy (Journal of Environmental Chemical Engineering, 2023)

Peculiar sleep features in sympatric species may contribute to the temporal segregation - Sukriti Mishra; Nisha Sharma; Sunil Kumar Singh; Shahnaz Rahman Lone (Journal of Comparative Physiology B, 2023)

Comparative Assessment of Remediation Potential of Xanthium strumarium Ecotypes in NaCl-Affected Root Zone - Noreen Akhter; Muhammad Aqeel; Muhammad Faisal Maqsood; Saher Nawaz; Muhammad Muslim Shahnaz; Noreen Khalid; Mohammed A. Basahi; Omar Mahmoud Al-Zoubi; Talaat Habeeb; Romina Alina Marc; Muhammad Kashif Irshad; Ali Noman (Water, Air, & Soil Pollution, 2022)

Spatial distribution of flood vulnerability index in Ardabil province, Iran - Elham Azizi; Raoof Mostafazadeh; Zeinab Hazbavi; Abazar Esmali Ouri; Shahnaz Mirzaie; Guangwei Huang; Xuepeng Qian (Stochastic Environmental Research and Risk Assessment, 2022)

Chemical constituents from the seed husks of Oryza sativa L. - Mohammed Ali; Ateeque Ahmad; Shahnaz Sultana; Showkat Rasool Mir (Natural Product Research, 2022)

Prevalence of Antibiotic-Resistant Lactobacilli in Sepsis Patients with Long-Term Antibiotic Therapy - Negin Yarahmadi; Shahnaz Halimi; Parnia Moradi; Mohammad Hossein Zamanian; Akram Rezaei; Siavash Vaziri; Alisha Akya; Amirhooshang Alvandi; Shaghayegh Yazdani; Darab Ghadimi; Jale Moradi (Current Microbiology, 2022)

Exosomes Derived Neuronal Markers: Immunoaffinity Isolation and Characterization - Ghada Yousif; Shahnaz Qadri; Aijaz Parray; Naveed Akhthar; Ashfaq Shuaib; Yousef Haik (NeuroMolecular Medicine, 2022)

GIS-based flood susceptibility mapping of the lower Bagmati basin in Bihar, using Shannon’s entropy model - Sohidul Islam; Mary Tahir; Shahnaz Parveen (Modeling Earth Systems and Environment, 2022)

Serum Brain-Derived Neurotrophic Factor (BDNF) in COVID-19 Patients and its Association with the COVID-19 Manifestations - Ali Asgarzadeh; Nasrin Fouladi; Vahid Asghariazar; Shahnaz Fooladi Sarabi; Hamid Afzoun Khiavi; Mahsa Mahmoudi; Elham Safarzadeh (Journal of Molecular Neuroscience, 2022)

Willingness to pay for adopting conservation tillage technologies in wheat cultivation: policy options for small-scale farmers - Shahnaz Begum Nazu; Sourav Mohan Saha; Md. Emran Hossain; Sadika Haque; Md. Akhtaruzzaman Khan (Environmental Science and Pollution Research, 2022)

Chitosan Scaffold Containing Periostin Enhances Sternum Bone Healing and Decreases Serum Level of TNF-α and IL-6 after Sternotomy in Rat - Mehdi Salehiamin; Heidar Toolee; Mahmoud Azami; Seyed Hossein Ahmadi Tafti; Sina Mojaverrostami; Shahnaz Halimi; Shogoofa Barakzai; Aligholi Sobhani; Yasaman Abbasi (Tissue Engineering and Regenerative Medicine, 2022)

Deeper in the blues: DNA barcoding of fishes from Pakistani coast of the Arabian Sea reveals overlooked genetic diversity - Shabir Ali Amir; Baidong Zhang; Rafaqat Masroor; Yulong Li; Dong-Xiu Xue; Shahnaz Rashid; Naveed Ahmad; Safia Mushtaq; Jean-Dominique Durand; Jinxian Liu (Marine Biodiversity, 2022)

Insecticidal activity of the essential oils from yarrow (Achillea wilhelmsii L.) and sweet asafetida (Ferula assa-foetida L.) against Aphis gossypii Glover. (Hemiptera: Aphididae) under controlled laboratory conditions - Zohreh Koorki; Shahnaz Shahidi-Noghabi; Guy Smagghe; Kamran Mahdian (International Journal of Tropical Insect Science, 2022)

The Role of Endoplasmic Reticulum and Mitochondria in Maintaining Redox Status and Glycolytic Metabolism in Pluripotent Stem Cells - Shahnaz Babaei-Abraki; Fereshteh Karamali; Mohammad Hossein Nasr-Esfahani (Stem Cell Reviews and Reports, 2022)

The assessment of lead concentration in raw milk collected from some major dairy farms in Iran and evaluation of associated health risk - Shahnaz Sharifi; Sara Sohrabvandi; Vahid Mofid; Fardin Javanmardi; Elham Khanniri; Amir Mohammad Mortazavian (Journal of Environmental Health Science and Engineering, 2022)

Feeding habits of three sparid breams, Argyrops spinifer Forsskål, 1775, Sparidentex hasta Valenciennes, 1830, and Rhabdosargus niger Tanaka & Iwatsuki, 2013 (family: Sparidae) in the coastal waters of Pakistan - Pirzada J. A. Siddiqui; Farkhanda Khan; Shahnaz Rashid; Safia Mushtaq; Habib Ul Hassan; Shabir Ali Amir (Marine Biodiversity, 2022)

Structural, Biochemical, and Physiological Adjustments for Toxicity Management, Accumulation, and Remediation of Cadmium in Wetland Ecosystems by Typha domingensis Pers - Noreen Akhter; Omey Habiba; Mehwish Hina; Muhammad Muslim Shahnaz; Fahad Mohammed Alzuaibr; Saad Alamri; Mohamed Hashem; Noreen Khalid; Muhammad Aqeel; Ali Noman (Water, Air, & Soil Pollution, 2022)

Dihydroquinazolin-4(1H)-one derivatives as novel and potential leads for diabetic management - Oluwatoyin Babatunde; Shehryar Hameed; Uzma Salar; Sridevi Chigurupati; Abdul Wadood; Ashfaq Ur Rehman; Vijayan Venugopal; Khalid Mohammed Khan; Muhammad Taha; Shahnaz Perveen (Molecular Diversity, 2022)

Oxidative Stress Indices Changes in the Hearts of Rat Pups in Response to Maternal Buprenorphine Treatment during Gestation and Lactation - Hamed Aramjoo; Shahnaz Yousefizadeh; Michael Aschner; Babak Roshanravan; Tahereh Farkhondeh; Saeed Samarghandian (Cardiovascular Toxicology, 2022)

Natural variation in the fast phase of chlorophyll a fluorescence induction curve (OJIP) in a global rice minicore panel - Naveed Khan; Jemaa Essemine; Saber Hamdani; Mingnan Qu; Ming-Ju Amy Lyu; Shahnaz Perveen; Alexandrina Stirbet; Govindjee Govindjee; Xin-Guang Zhu (Photosynthesis Research, 2021)

Morpho-cultural, physiological and molecular characterisation of Sphaceloma ampelinum causing anthracnose of grapes in temperate region of India and its management - Uzma Fayaz; Saba Banday; Efath Shahnaz; N. A. Khan; Sajad Majeed Zargar; Arif Hussain Bhat (Indian Phytopathology, 2021)

Spatiotemporal variability of trend in extreme precipitations using fuzzy clustering over Northwest Iran - Marziyeh Esmaeilpour; Ahmad Reza Ghasemi; Farahnaz Khoramabadi; Shahnaz Rashedi (Earth Science Informatics, 2021)

Multidimensional analysis of global climate change: a review - Suhaib A. Bandh; Sana Shafi; Mohazeb Peerzada; Tanzeela Rehman; Shahnaz Bashir; Shahid A. Wani; Rubiya Dar (Environmental Science and Pollution Research, 2021)

Short-term effects of air pollutants on hospitalization rate in patients with cardiovascular disease: a case-crossover study - Leily Sokoty; Shahnaz Rimaz; Babak Hassanlouei; Majid Kermani; Leila Janani (Environmental Science and Pollution Research, 2021)

Physiological homeostasis for ecological success of Typha (Typha domingensis Pers.) populations in saline soils - Noreen Akhter; Muhammad Aqeel; Muhammad Muslim Shahnaz; Ghalia S. H. Alnusairi; Suliman Mohammed Alghanem; Abida Kousar; Mohamed Hashem; Hina Kanwal; Saad Alamri; Aisha Ilyas; Omar Mahmoud Al-zoubi; Ali Noman (Physiology and Molecular Biology of Plants, 2021)

Regeneration of Rat Sciatic Nerve Using PLGA Conduit Containing Rat ADSCs with Controlled Release of BDNF and Gold Nanoparticles - Maliheh Jahromi; Shahnaz Razavi; Reihaneh Seyedebrahimi; Parham Reisi; Mohammad Kazemi (Journal of Molecular Neuroscience, 2021)

Modulations of obesity-related microRNAs after exercise intervention: a systematic review and bioinformatics analysis - Naeim Ehtesham; Shahnaz Shahrbanian; Mohammad Valadiathar; Seyed Javad Mowla (Molecular Biology Reports, 2021)

Revisiting time to translation: implementation of evidence-based practices (EBPs) in cancer control - Shahnaz Khan; David Chambers; Gila Neta (Cancer Causes & Control, 2021)

Biology-oriented drug synthesis (BIODS), in vitro urease inhibitory activity, and in silico studies on ibuprofen derivatives - Faiza Seraj; Kanwal; Khalid Mohammed Khan; Ajmal Khan; Muhammad Ali; Ruqaiya Khalil; Zaheer Ul-Haq; Shehryar Hameed; Muhammad Taha; Uzma Salar; Shahnaz Perveen (Molecular Diversity, 2021)

Dihydropyrimidones: A ligands urease recognition study and mechanistic insight through in vitro and in silico approach - Farman Ali Khan; Shahbaz Shamim; Nisar Ullah; Muhammad Arif Lodhi; Khalid Mohammed Khan; Kanwal; Farman Ali; Sahib Gul Afridi; Shahnaz Perveen; Ajmal Khan (Medicinal Chemistry Research, 2021)

Innate immune response in systemic autoimmune diseases: a potential target of therapy - Alireza Hejrati; Alireza Rafiei; Mohsen Soltanshahi; Shahnaz Hosseinzadeh; Mina Dabiri; Mahdi Taghadosi; Saeid Taghiloo; Davood Bashash; Fatemeh Khorshidi; Parisa Zafari (Inflammopharmacology, 2020)

Improvement of Remyelination in Demyelinated Corpus Callosum Using Human Adipose-Derived Stem Cells (hADSCs) and Pregnenolone in the Cuprizone Rat Model of Multiple Sclerosis - Rasoul Ganji; Shahnaz Razavi; Nazem Ghasemi; Mohammad Mardani (Journal of Molecular Neuroscience, 2020)

Multi-functionalized nanocarriers targeting bacterial reservoirs to overcome challenges of multi drug-resistance - Maria Hassan Kiani; Muhammad Imran; Abida Raza; Gul Shahnaz (DARU Journal of Pharmaceutical Sciences, 2020)

Comparative assessment of raw and acid-activated preparations of novel Pongamia pinnata shells for adsorption of hexavalent chromium from simulated wastewater - Chandi Patra; Tasrin Shahnaz; Senthilmurugan Subbiah; Selvaraju Narayanasamy (Environmental Science and Pollution Research, 2020)

Kinetic and thermodynamic studies on biosorption of Cr(VI) on raw and chemically modified Datura stramonium fruit - Shravan Kumar; Tasrin Shahnaz; N. Selvaraju; Prasanna Venkatesh Rajaraman (Environmental Monitoring and Assessment, 2020)

Therapeutic effects of Cyperus rotundus rhizome extract on memory impairment, neurogenesis and mitochondria in beta-amyloid rat model of Alzheimer’s disease - Zeinab Shakerin; Ebrahim Esfandiari; Mustafa Ghanadian; Shahnaz Razavi; Hojjatallah Alaei; Gholamreza Dashti (Metabolic Brain Disease, 2020)

Human bocavirus infections and co-infections with respiratory syncytial virus and Rotavirus in children with acute respiratory or gastrointestinal disease - Mehrdad Mohammadi; Shahnaz Armin; Zahra Yazdanpour (Brazilian Journal of Microbiology, 2020)

circRNAs expressed in human peripheral blood are associated with human aging phenotypes, cellular senescence and mouse lifespan - Shahnaz Haque; Ryan M. Ames; Karen Moore; Luke C. Pilling; Luanne L. Peters; Stefania Bandinelli; Luigi Ferrucci; Lorna W. Harries (GeroScience, 2020)
Circular RNAs (circRNAs) are an emerging class of non-coding RNA molecules that are thought to regulate gene expression and human disease. Despite the observation that circRNAs are known to accumulate in older organisms and have been reported in cellular senescence, their role in aging remains relatively unexplored. Here, we have assessed circRNA expression in aging human blood and followed up age-associated circRNA in relation to human aging phenotypes, mammalian longevity as measured by mouse median strain lifespan and cellular senescence in four different primary human cell types. We found that circRNAs circDEF6 , c ircEP300 , circFOXO3 and circFNDC3B demonstrate associations with parental longevity or hand grip strength in 306 subjects from the InCHIANTI study of aging, and furthermore, circFOXO3 and circEP300 also demonstrate differential expression in one or more human senescent cell types. Finally, four circRNAs tested showed evidence of conservation in mouse. Expression levels of one of these, circPlekhm1 , was nominally associated with lifespan. These data suggest that circRNA may represent a novel class of regulatory RNA involved in the determination of aging phenotypes, which may show future promise as both biomarkers and future therapeutic targets for age-related disease.

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Development and Characterization of Bioadhesive Film Embedded with Lignocaine and Calcium Fluoride Nanoparticles - Hira Ghafar; Muhammad Imran Khan; Hafiz Shoaib Sarwar; Samiya Yaqoob; Syed Zajif Hussain; Imran Tariq; Asad Ullah Madni; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Application of Hanging Drop Culture for Retinal Precursor-Like Cells Differentiation of Human Adipose-Derived Stem Cells Using Small Molecules - Hossein Salehi; Shahnaz Razavi; Ebrahim Esfandiari; Mohammad Kazemi; Shahram Amini; Noushin Amirpour (Journal of Molecular Neuroscience, 2019)

Hexavalent chromium adsorption on virgin, biochar, and chemically modified carbons prepared from Phanera vahlii fruit biomass: equilibrium, kinetics, and thermodynamics approach - Abhishek Ajmani; Tasrin Shahnaz; Senthilmurugan Subbiah; Selvaraju Narayanasamy (Environmental Science and Pollution Research, 2019)

Formulation and Evaluation of Novel Thiolated Intra Pocket Periodontal Composite Membrane of Doxycycline - Asma Kanwal; Ali Iqbal; Rabia Arshad; Sohail Akhtar; Sobia Razzaq; Nasir Mahmood Ahmad; Hina Naz; Gul Shahnaz (AAPS PharmSciTech, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Hesperetin is a potent bioactivator that activates SIRT1-AMPK signaling pathway in HepG2 cells - Hajar Shokri Afra; Mohammad Zangooei; Reza Meshkani; Mohammad Hossein Ghahremani; Davod Ilbeigi; Azam Khedri; Shiva Shahmohamadnejad; Shahnaz Khaghani; Mitra Nourbakhsh (Journal of Physiology and Biochemistry, 2019)

Removal of Cu(II), Pb(II) and Cr(VI) ions from aqueous solution using amidoximated non-woven polyethylene-g-acrylonitrile fabric - Nazia Rahman; Md. Shakhawat Hossen; Abdur Rahim Miah; Makid Maskawat Marjub; Nirmal Chandra Dafader; S. Shahnaz; M. F. Alam (Journal of Environmental Health Science and Engineering, 2019)

Changes in the photosynthesis properties and photoprotection capacity in rice (Oryza sativa) grown under red, blue, or white light - Saber Hamdani; Naveed Khan; Shahnaz Perveen; Mingnan Qu; Jianjun Jiang; Govindjee; Xin-Guang Zhu (Photosynthesis Research, 2019)

SPECMAR: fast heart rate estimation from PPG signal using a modified spectral subtraction scheme with composite motion artifacts reference generation - Mohammad Tariqul Islam; Sk. Tanvir Ahmed; Celia Shahnaz; Shaikh Anowarul Fattah (Medical & Biological Engineering & Computing, 2019)

Folate-Functionalized Thiomeric Nanoparticles for Enhanced Docetaxel Cytotoxicity and Improved Oral Bioavailability - Muhammad Sajjad; Muhammad Imran Khan; Sara Naveed; Sana Ijaz; Omer Salman Qureshi; Syed Atif Raza; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2019)

Altered regulation of the T-cell system in patients with CRPS - Jens Heyn; Shahnaz C. Azad; Benjamin Luchting (Inflammation Research, 2019)

Synthesis, in vitro $$α $$ α -glucosidase inhibitory activity, and in silico study of (E)-thiosemicarbazones and (E)-2-(2-(arylmethylene)hydrazinyl)-4-arylthiazole derivatives - Muhammad Ali; Khalid Mohammed Khan; Uzma Salar; Mohammed Ashraf; Muhammad Taha; Abdul Wadood; Sujhla Hamid; Muhammad Riaz; Basharat Ali; Shahbaz Shamim; Farman Ali; Shahnaz Perveen (Molecular Diversity, 2018)

Simulation of surface runoff using semi distributed hydrological model for a part of Satluj Basin: parameterization and global sensitivity analysis using SWAT CUP - Shahnaz Khatun; Mehebub Sahana; Sanjay K. Jain; Neha Jain (Modeling Earth Systems and Environment, 2018)

The role of nonautologous and autologous adipose-derived mesenchymal stem cell in acute pyelonephritis - Shabnam Sabetkish; Nastaran Sabetkish; Mahba Ataei Talebi; Shahnaz Halimi; Abdol-Mohammad Kajbafzadeh (Cell and Tissue Banking, 2018)

CBS mutations and MTFHR SNPs causative of hyperhomocysteinemia in Pakistani children - Shahnaz Ibrahim; Saadia Maqbool; Maleeha Azam; Mohammad Perwaiz Iqbal; Raheel Qamar (Molecular Biology Reports, 2018)

Effects of nickel toxicity on morphological and physiological aspects of osmoregulation in Typha domingensis (Typhaceae) populations - Noreen Akhtar; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Khawaja Shafique Ahmad; Jiabin Deng; Ansar Mehmood; Claudia Segovia-Salcedo; Muhammad Muslim Shahnaz; Abdul Qadir Khan (Limnology, 2018)

The Association Between Effective Dose of Magnesium and Mild Compulsive Exercise on Spatial Learning, Memory, and Motor Activity of Adult Male Rats - Shahnaz Hajizade Ghonsulakandi; Mahmuod Sheikh; Marzieh Dehghan Shasaltaneh; Samira Chopani; Nasser Naghdi (Biological Trace Element Research, 2017)

Formulation and In Vitro Characterization of Thiolated Buccoadhesive Film of Fluconazole - Kiran Naz; Gul Shahnaz; Naveed Ahmed; Naveeda Akhtar Qureshi; Hafiz Shoaib Sarwar; Muhammad Imran; Gul Majid Khan (AAPS PharmSciTech, 2017)

RETRACTED ARTICLE: The Effect of Zinc Supplementation on Expressed Levels of Peroxisome Proliferator-Activated Receptor Gamma and Glucose Transporter Type 1 Genes in Newborns of Women with Gestational Diabetes Mellitus - Zahra Heidarzadeh; Mansooreh Samimi; Seyed Morteza Seifati; Mahmood Dehghani Ashkezari; Shahnaz Ahmadi; Samaneh Mahmoodi; Esmat Aghadavod; Mehri Jamilian; Zatollah Asemi (Biological Trace Element Research, 2017)

The Time Course of Activity within the Dorsal and Rostral-Ventral Anterior Cingulate Cortex in the Emotional Stroop Task - Farah Shahnaz Feroz; Gregor Leicht; Saskia Steinmann; Christina Andreou; Christoph Mulert (Brain Topography, 2017)

Effect of Laminin on Neurotrophic Factors Expression in Schwann-Like Cells Induced from Human Adipose-Derived Stem Cells In Vitro - Giti Zarinfard; Mina Tadjalli; Shahnaz Razavi; Mohammad Kazemi (Journal of Molecular Neuroscience, 2016)

Effect of different natural and factitious diets on development and life history parameters of Chilocorus bipustulatus - Haniieh Atrchian; Kamran Mahdian; Shahnaz Shahidi (BioControl, 2016)

Synthesis and urease inhibitory activities of benzophenone semicarbazones/thiosemicarbazones - Arshia Arshia; Ajmal Khan; Khalid Mohammed Khan; Syed Muhammad Saad; Nida Iqbal Siddiqui; Sumaira Javaid; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Biomechanical Properties and Microstructure of Heart Chambers: A Paired Comparison Study in an Ovine Model - Shahnaz Javani; Matthew Gordon; Ali N. Azadani (Annals of Biomedical Engineering, 2016)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

Piroxicam sulfonates biology-oriented drug synthesis (BIODS), characterization and anti-nociceptive screening - Safi Ullah; Muhammad Saeed; Syed Muhammad Ashhad Halimi; Muhammad Imran Fakhri; Khalid Mohammed Khan; Ikhtiar Khan; Shahnaz Perveen (Medicinal Chemistry Research, 2016)

Antioxidant, cholinesterase inhibition activities and essential oil analysis of Nelumbo nucifera seeds - Shahnaz Khan; Hidayatullah Khan; Farman Ali; Nayab Ali; Fahim Ullah Khan; Sami Ullah Khan (Natural Product Research, 2016)

Purification and biochemical characterisation of acid phosphatase-I from seeds of Nelumbo nucifera - Sanaullah Khan; Shahnaz Khan; Sajida Batool; Mushtaq Ahmed (Natural Product Research, 2016)

A re-interpretation of impact of the Icelandic Low and Azores High on winter precipitation over Iberian Peninsula - M. J. Iqbal; Shahnaz Feroz Rashid (Arabian Journal of Geosciences, 2016)

Synthesis of phenyl thiazole hydrazones and their activity against glycation of proteins - Khalid Mohammed Khan; Muhammad Irfan; Mahwish Ashraf; Muhammad Taha; Syed Muhammad Saad; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2015)

Combining ability through line × tester analysis for phenological, seed yield, and oil traits in sunflower (Helianthus annuus L.) - Shahnaz Memon; Muhammad Jurial Baloch; Gul Muhammad Baloch; Wajid Ali Jatoi (Euphytica, 2015)

The cyanobacterium Synechocystis sp. PUPCCC 62: a potential candidate for biotransformation of Cr(VI) to Cr(III) in the presence of sulphate - Shahnaz Parveen; J. I. S. Khattar; D. P. Singh (Environmental Science and Pollution Research, 2015)

Quantitative trait loci mapping of partial resistance to Diamondback moth in cabbage (Brassica oleracea L) - Nirala Ramchiary; Wenxing Pang; Van Dan Nguyen; Xiaonan Li; Su Ryun Choi; Ajay Kumar; Min Kwon; Hye Young Song; Shahnaz Begum; Mechuselie Kehie; Moo-Kyoung Yoon; Jonghyun Na; et al. (Theoretical and Applied Genetics, 2015)

Intracellular uptake and reduction of hexavalent chromium by the cyanobacterium Synechocystis sp. PUPCCC 62 - J. I. S. Khattar; Shahnaz Parveen; Y. Singh; D. P. Singh; A. Gulati (Journal of Applied Phycology, 2015)

Assessment of genotoxic and humoral immune system alterations in silica exposed workers from pottery industries in South India - Balasubramanian Balamuralikrishnan; Vellingiri Balachandar; Mohana Devi Subramaniam; Karthick Kumar Alagumuthu; Shanmugam Sureshkumar; Meyyazhagan Arun; Sundaramoorthy Arun; Krishnan Padmavathi; Abdul Hakkim Razeena; Mohan Gomathi; Palanivel Velmurugan; Shahnaz N. Dharwadkar; et al. (Stochastic Environmental Research and Risk Assessment, 2014)

2-(2′-Pyridyl) benzimidazole derivatives and their urease inhibitory activity - Zafar Saeed Saify; Arfa Kamil; Shamim Akhtar; Muhammad Taha; Ajmal Khan; Khalid Mohammed Khan; Sarwat Jahan; Fazal Rahim; Shahnaz Perveen; M. Iqbal Choudhary (Medicinal Chemistry Research, 2014)

Unsymmetrical 1,3-disubstituted urea derivatives as α-chymotrypsin inhibitors - Shahnaz Perveen; Sana Mustafa; Mehreen Latif; Lubna Iqbal; Tanzil H. Usmani; Khalid Mohammed Khan; Wolfgang Voelter (Medicinal Chemistry Research, 2014)

Quantification of malachite green in fish feed utilising liquid chromatography-tandem mass spectrometry with a monolithic column - Kamran Abro; Sarfaraz Ahmed Mahesar; Seema Iqbal; Shahnaz Perveen (Food Additives & Contaminants: Part A, 2014)

Evaluation of the thiazole Schiff bases as $$\upbeta $$ β -glucuronidase inhibitors and their in silico studies - Khalid Mohammed Khan; Aneela Karim; Sumayya Saied; Nida Ambreen; Xayale Rustamova; Shagufta Naureen; Sajid Mansoor; Muhammad Ali; Shahnaz Perveen; M. Iqbal Choudhary; Guillermo Antonio Morales (Molecular Diversity, 2014)

Antiproliferative effects of novel urea derivatives against human prostate and lung cancer cells; and their inhibition of β-glucuronidase activity - Shahnaz Perveen; Sana Mustafa; Kehkashan Qamar; Ahsana Dar; Khalid M. Khan; Muhammad Iqbal Choudhary; Ajmal Khan; Wolfgang Voelter (Medicinal Chemistry Research, 2014)

2,5-Disubstituted-1,3,4-oxadiazoles: thymidine phosphorylase inhibitors - Khalid Mohammed Khan; Mubeen Rani; Nida Ambreen; Muhammad Ali; Sajjad Hussain; Shahnaz Perveen; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Rapid in vitro multiplication and ex vitro establishment of Caribbean copper plant (Euphorbia cotinifolia L.): an important medicinal shrub - Shahnaz Perveen; Saad Bin Javed; M. Anis; Ibrahim M. Aref (Acta Physiologiae Plantarum, 2013)

SH3GL2 is frequently deleted in non-small cell lung cancer and downregulates tumor growth by modulating EGFR signaling - Santanu Dasgupta; Jin Sung Jang; Chunbo Shao; Nitai D. Mukhopadhyay; Upneet K. Sokhi; Swadesh K. Das; Mariana Brait; Conover Talbot; Rex C. Yung; Shahnaz Begum; William H. Westra; Mohammad Obaidul Hoque; et al. (Journal of Molecular Medicine, 2013)

Mating compatibility and competitiveness of transgenic and wild type Aedes aegypti (L.) under contained semi-field conditions - H. L. Lee; Seshadri Vasan; Nazni Wasi Ahmad; Iswarti Idris; Norhaida Hanum; S. Selvi; Luke Alphey; Shahnaz Murad (Transgenic Research, 2013)

Simultaneous Inhibition of COX-2 and Activation of PPAR-γ Resulted in the Same Level and Pattern of Neuroprotection as They were Targeted Separately - Shahnaz Babaei Abraki; Leila Khalaj; Fatemeh Shaerzadeh; Fariba Khodagholi (Journal of Molecular Neuroscience, 2013)

RETRACTED ARTICLE: Increase of autophagy and attenuation of apoptosis by Salvigenin promote survival of SH-SY5Y cells following treatment with H2O2 - Ghazaleh Rafatian; Fariba Khodagholi; Mahdi Moridi Farimani; Shahnaz Babaei Abraki; Mossa Gardaneh (Molecular and Cellular Biochemistry, 2012)

The Effect of Pretreatment of Juice on the Properties and Composition of Jaggery - Zahid Hussain; Mohammad Islam; Zahoor Mohammad; Khalid Mohammad Khan; Shahnaz Perveen; Mohammad Afzal (Sugar Tech, 2012)

Antidepressant activity of carbamates and urea derivatives - Shahnaz Perveen; Nasreen Fatima; Muhammad Aitmaud Khan; Ahsana Dar; Khalid M. Khan; Nighat Afza; Wolfgang Voelter (Medicinal Chemistry Research, 2012)

Analytical variables influencing the HCV RNA determination by TaqMan real-time PCR in routine clinical laboratory practice - Abida Raza; Zameer Ali; Javaid Irfan; Shahnaz Murtaza; Samina Shakeel (Molecular Biology Reports, 2012)

In vitro morphogenic response and metal accumulation in Albizia lebbeck (L.) cultures grown under metal stress - Shahnaz Perveen; Mohammad Anis; I. M. Aref (European Journal of Forest Research, 2012)

Serum Selenium Concentration in Liver Cirrhotic Patients Suffering from Hepatitis B and C in Pakistan - Naseem Rauf; S. S. Tahir; Shahnaz Dilawar; Irshad Ahmad; Shoukat Parvez (Biological Trace Element Research, 2012)

Matrix metalloproteinas-9 functional promoter polymorphism 1562C>T increased risk of early-onset coronary artery disease - Massoud Saedi; Asad Vaisi-Raygani; Shahnaz Khaghani; Ahmad Shariftabrizi; M. Rezaie; Parvin Pasalar; Zohreh Rahimi; Tayebeh Pourmotabbed (Molecular Biology Reports, 2012)

The Effect of Contact Surface on the Properties of Jaggery - Zahid Hussain; Mohammad Islam; Fida Mohammad; Shahnaz Perveen; Khalid Mohammad Khan (Sugar Tech, 2011)

Inhibition of chemiluminescence and chemotactic activity of phagocytes in vitro by the extracts of selected medicinal plants - Ibrahim Jantan; Nurul Hikmah Harun; Abdi Wira Septama; Shahnaz Murad; M. A. Mesaik (Journal of Natural Medicines, 2011)

Effect of successive increase in alcohol chains on reaction with isocyanates and isothiocyanates - Shahnaz Perveen; Arfa Yasmin; Khalid Mohammed Khan (Natural Product Research, 2010)

Expression of Sambucus nigra agglutinin (SNA-I′) from elderberry bark in transgenic tobacco plants results in enhanced resistance to different insect species - Shahnaz Shahidi-Noghabi; Els J. M. Van Damme; Guy Smagghe (Transgenic Research, 2009)

Leishmanicidal potential of N-substituted morpholine derivatives: Synthesis and structure–activity relationships - Khalid Mohammed Khan; Muhammad Zarrar Khan; Muhammad Taha; Ghulam Murtaza Maharvi; Zafar Saeed Saify; Shahnaz Parveen; Muhammad Iqbal Choudhary (Natural Product Research, 2009)

Facile, economical and direct synthesis of 9-anilinoacridines - Khalid M. Khan; Nosheen A. Rao; Zia-Ullah; Muhammad Ali; Shahnaz Perveen; Muhammad Iqbal Choudhary; Atta-Ur-Rahman; Wolfgang Voelter (Natural Product Research, 2009)

A convenient iodination method for alcohols using cesium iodide/methanesulfonic acid and its comparison using cesium iodide/ p -toluenesulfonic acid or cesium iodide/aluminium chloride - Khalid Mohammed Khan; Shahnaz Perveen; Safdar Hayat; Muhammad Ali; Wolfgang Voelter (Natural Product Research, 2008)

An expeditious and environmentally friendly synthesis of 3-substituted isocoumarins using microwave irradiation - Khalid Mohammed Khan; Sumbul Ahmed; Zulfiqar Ali Khan; Mubeen Rani; Shahnaz Perveen; Wolfgang Voelter (Natural Product Research, 2008)

An improved method of synthesis of N -protected L -amino acids as their benzoxymethyl esters - Javid Hussain Zaidi; Muhammad Arfan; Saadullah Mir; Jabbar Hussain Shah; Shahnaz Perveen; Khalid Mohammed Khan (Natural Product Research, 2008)

1 H NMR, mass spectroscopic studies and color fastness properties of methyl-4,6-dihydroxy-2-oxo-1-phenyl-5-arylazopyridine-3-carboxylate, part III: new disperse dyes - Rasheeda Parveen; Shahnaz Perveen; Ausaf Aleem; Khalid M. Khan; Mahwish (Natural Product Research, 2007)

Iron and cadmium uptake by duodenum of hypotransferrinaemic mice - Kishor B. Raja; Shahnaz E. Jafri; Timothy J. Peters; Robert J. Simpson (BioMetals, 2006)

Piperidines: A new class of Urease inhibitors - Khalid Mohammed Khan; Zafar S. Saify; Muhammad Arif Lodhi; Naeem Butt; Shahnaz Perveen; Ghulam Murtaza Maharvi; Muhammad Iqbal Choudhary; Atta-ur-rahman (Natural Product Research, 2006)

Alternative method of Boc-removal from sulfamide using silica-phenyl sulfonic acid in conjunction with microwave heating - Shahnaz Ghassemi; Kristin Fuchs (Molecular Diversity, 2005)

A facile and improved synthesis of sildenafil (Viagra) analogs through solid support microwave irradiation possessing tyrosinase inhibitory potential, their conformational analysis and molecular dynamics simulation studies - Khalid M. Khan; Ghulam M. Maharvi; Mahmud T. H. Khan; Shahnaz Perveen; Muhammad I. Choudhary; Atta-ur- Rahman (Molecular Diversity, 2005)